Automatic block decomposition based on dual surfaces. (October 2020) - Zheng, Zhihao; Wang, Rui; Gao, Shuming; Liao, Yizhou; Ding, Mao
Abstract: A high-quality block structure of a 3D model can support many important applications; however, the automated generation of a high-quality block structure is still a challenging problem. In this paper, a dual surface-based approach to automated and valid block decomposition of 3D models is proposed. First, dual loops for block decomposition are generated with the help of a computed frame field whose three types of degenerated singularities are corrected. Then, a required dual surfaces set is constructed to suitably separate all the boundary elements of the 3D model and singularities of the frame field with the help of the basis of the non-trivial loops on the boundary surfaces. Finally, a valid block structure is obtained by performing dual operations along the dual surfaces on the hex mesh generated by splitting the tetrahedral mesh of the 3D model. Experimental results showed the effectiveness of the proposed approach. Graphical abstract: Highlights: The method can automatically generate a block structure of a 3D model based on dual surfaces. The constructed dual surfaces set can separate all the geometric elements and simple singular polylines. The topological validity of the obtained block structure can be guaranteed. The construction of dual surfaces is guided by the high-quality frame field with 35 polylines corrected. The basis of handle and tunnel loops on surface is used to help the construction of dual surfaces.